2023
DOI: 10.21203/rs.3.rs-2466890/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell multi-omics analysis identifies two distinct phenotypes of newly-onset microscopic polyangiitis

Abstract: Patients with autoimmune vasculitis present with diverse organ-threatening symptoms, but the underlying immunological basis of the clinical heterogeneity remains poorly understood. We conducted single-cell transcriptome and surface proteome analyses using CITE-seq on 109,350 peripheral blood mononuclear cells (PBMCs) and CyTOF on 737,794 PBMCs from newly-onset patients with microscopic polyangiitis (MPA) and age-matched healthy donors. Increased proportions of activated CD14+ monocytes, CD14+ monocytes express… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…There are mixed findings on monocyte composition in AAV (4), similar to the field of CVD (32). Whereas in most CVD studies an increased percentage of IM and NCM was found (32), in AAV, upregulation of CM appears intricately linked to the underlying pathophysiology of the disease, as shown by a recent single-cell RNA sequencing study, highlighting a link between the expansion of activated and interferon signature expressing classical monocyte subsets and resistance to therapy and kidney infiltration (33, 34). As expected, the CM subset expressed high CCR2 levels, and it was found that CCR2 was associated with arterial wall inflammation (35).…”
Section: Discussionmentioning
confidence: 99%
“…There are mixed findings on monocyte composition in AAV (4), similar to the field of CVD (32). Whereas in most CVD studies an increased percentage of IM and NCM was found (32), in AAV, upregulation of CM appears intricately linked to the underlying pathophysiology of the disease, as shown by a recent single-cell RNA sequencing study, highlighting a link between the expansion of activated and interferon signature expressing classical monocyte subsets and resistance to therapy and kidney infiltration (33, 34). As expected, the CM subset expressed high CCR2 levels, and it was found that CCR2 was associated with arterial wall inflammation (35).…”
Section: Discussionmentioning
confidence: 99%
“…To analyze in-depth pro les of each cell population using single-cell transcriptomes, we further subdivided each cell population using previously reported marker genes [13][14][15][16] . UMAP plots of monocyte subsets and pro les of highly expressed genes are provided in Extended Data Fig.…”
Section: Table 1 Clinical Characteristics Of Systemic Sclerosis Patie...mentioning
confidence: 99%
“…CITE-seq was performed using the same antibodies as in our previous report 15 . Thawed PBMCs were treated with DNA-barcoded antibodies, and single-cell suspensions were processed using the 10x Genomics Chromium Controller (10x Genomics).…”
Section: Single-cell Library Construction (Cite-seq)mentioning
confidence: 99%
“…Moreover, recent ow cytometric, single cell RNA sequencing (scRNA-seq) and immunohistochemical analyses of kidney biopsy samples have provided deeper insights into pathomechanisms of immune cells in ANCA-GN [12][13][14][15] . However, the relevant speci c spatial localization of immune cells, and their cellular interactions are largely unknown.…”
Section: Introductionmentioning
confidence: 99%